Association of Waist and Hip Ratio with the Angiographic Severity of Coronary Artery Disease in Patients with Non ST Segment Elevation Myocardial Infarction - Haque, Md Mozammel; Rashid, Md Mamunur; Ali, Md Zulfikar; Alam, Iftekhar; Ahmed, Md Sukur; Mamun, Al; Shil, Tapan Chandra; Mallick, Golam Rahman; Khan, Mahbubur Rahman; Ghosh, Tamal Peter; et al. (Bangladesh Heart Journal, 2022)
Background: Obesity is a proven independent risk factor for coronary artery disease. There are different Methods for evaluation of obesity. The aim of this study is to evaluate the association between waist hip ratio and the severity of CAD in non-ST-segment elevation myocardial infarction patients. Methods: This cross-sectional observational study was done at the National Institute of Cardiovascular Diseases (NICVD), Dhaka. A total of 100 patients with NSTEMI who underwent coronary angiogram during the indexed hospitalization period were included in this study. On the basis of WHR, study patients were divided into two groups 50 patients of NSTEMI with normal WHR (Male <0.90, Female <0.80) were assigned as group I and 50 patients of NSTEMI with increased WHR (Male ³0.90, Female ³0.80) were assigned as group II. Results: The mean age of patients was 49.6±7.9 years and 52.3±8.7 years in Group I and Group II respectively with a male predominance in both the groups. No significant difference was found in between two groups in terms of demographic characteristics and traditional risk factors for CAD. Different parameters of angiographic severity of CAD were significantly higher in patients with increased WHR. Patients with non critical CAD (14% vs 0%, P = 0.02) and single vessel disease (58% vs 24%, P = 0.005) were more frequent in Group I, on the contrary double vessel disease (24% vs. 56%, P = 0.001) and triple vessel disease (4% vs. 20%, P = 0.03) were significantly more frequent in patients of Group II. Patients with moderate to severe CAD (Gensini score ³36) were found more in Group II than that of in Group I (24% vs. 76%, P <0.001) and there was statistically significant higher Gensini score was found in Group II (21.96±19.72 vs. 44.18±28.91, P <0.001). Significant positive correlation was found in between WHR and coronary artery disease severity measured by vessel score (r = 0.41, P < 0.001) and Gensini score (r = 0.31, P< 0.001). Multivariate regression analysis yielded that the risk of having significant CAD are 3.45 times more in patients with increased WHR than those of normal WHR (95% CI: 1.229-12.979, P = 0.01). Conclusion: Abdominal obesity, as evidenced by increased WHR, may be considered as a predictor of the severity of CAD in patients with acute NSTEMI. Bangladesh Heart Journal 2022; 37(2): 122-129